Optimalisasi Sarana dan Prasarana BK Dalam Mendukung Kegiatan Manajemen Bimbingan Konseling yang Efektif di SMA Negeri 2 Palembayan - Halimahtun Syaddiyah; Neviyarni S; Yarmis Syukur (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The focus of this study is to optimize guidance and counseling facilities and infrastructure to support effective G&C service management at SMA Negeri 2 Palembayan. Facilities and infrastructure are important components that influence service quality, counselor capabilities, and the successful achievement of student development goals. This study aims to describe the role of facilities and infrastructure in supporting effective counseling management in schools and the forms of optimization that can be carried out. The method used is a literature study with a descriptive-qualitative approach through a review of various literature sources in the form of books, scientific journals, and education regulations. The results of the study show that the optimization of guidance and counseling facilities and infrastructure can improve service quality, ensure counseling confidentiality, strengthen administration, and enhance the professionalism of guidance and counseling teachers. Thus, the optimal management of guidance and counseling facilities and infrastructure is an important requirement in realizing effective and quality guidance and counseling services at SMA Negeri 2 Palembayan.